If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(5s + -2) + -4 = -2(8s + 10) + -3 Reorder the terms: -2(-2 + 5s) + -4 = -2(8s + 10) + -3 (-2 * -2 + 5s * -2) + -4 = -2(8s + 10) + -3 (4 + -10s) + -4 = -2(8s + 10) + -3 Reorder the terms: 4 + -4 + -10s = -2(8s + 10) + -3 Combine like terms: 4 + -4 = 0 0 + -10s = -2(8s + 10) + -3 -10s = -2(8s + 10) + -3 Reorder the terms: -10s = -2(10 + 8s) + -3 -10s = (10 * -2 + 8s * -2) + -3 -10s = (-20 + -16s) + -3 Reorder the terms: -10s = -20 + -3 + -16s Combine like terms: -20 + -3 = -23 -10s = -23 + -16s Solving -10s = -23 + -16s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '16s' to each side of the equation. -10s + 16s = -23 + -16s + 16s Combine like terms: -10s + 16s = 6s 6s = -23 + -16s + 16s Combine like terms: -16s + 16s = 0 6s = -23 + 0 6s = -23 Divide each side by '6'. s = -3.833333333 Simplifying s = -3.833333333
| 3x+10=18-x | | 16x^2-32x+80=0 | | 2x+6=5x+3 | | 87.5*200=x | | 2(3t+1)-5=t-(t-2) | | 5x-57=2x | | 34.99+.59=148.86 | | 4x+34=7 | | 4c+7=2c-3 | | 4c+7=2c-7 | | 10b^5+20b^2= | | (2x+5)(3x^2-10x+8)=0 | | 3x-9=-4x+5 | | 6+(-10)= | | 100*80= | | 3x+2x+6=30 | | 12-2(x+3)-4(3x+6)=10 | | 8x-3y=50 | | 25-13-(-47)+(-11)= | | 3x=2+6x-(5-2x) | | 4x+5-3x=11-3 | | -3x-4(2-x)=7 | | 72+-14=36 | | 4x-5=36x-2 | | 3x+2(x+3)=30 | | 3(x+1)=2x-(4-x) | | a(3tx-2b)=x(dx-2) | | 5n-n=9+3 | | 5n-n=9 | | 13x^2+10x+1=0 | | 4r^2-4r+1=0 | | 180-x=3(90-x)-38 |